Effects of supplementation with spray-dried porcine plasma on blood variables on piglets feed with diet contaminated by mycotoxins - Muller L.K.F.* (2017)
© 2017 Elsevier LtdThe aim of this study was to evaluate the supplementation spray-dried porcine plasma (SDPP) effects on body weight, glucose levels and hematological and immunology variables for piglets fed with diet contaminated with low or high aflatoxin and fumonisin levels. Thus, 24 piglets were allotted in four groups, and the group A received a control diet; the group B received a diet with 6% of SDPP; the group C 300 μg/kg of aflatoxins and 8000 μg/kg of fumonisin; the group D 300 μg/kg of aflatoxins, 8000 μg/kg of fumonisin and 6% of SDPP, respectively. A significant increase on hemoglobin concentration and hematocrit levels was observed between C and A groups, result similar also in group D to hemoglobin concentration. A significant reduction on leukocytes and monocytes levels was observed in the group C compared to group A. Most important finding was that SDPP prevented reduction on leukocytes, but not in the monocytes levels in animals of group D. Moreover, the animals of group C presented lower weight, in the same way presented lower on glucose levels. In the other hand, animals in the group C had higher levels of nitrate/nitrite (NOx) and C-reactive protein (CRP) compared other groups. Based on these evidences, the present study showed ingestion of diet contaminated with elevated aflatoxins and fumonisins levels may negatively affected the white cell count and the weight, increasing the seric biomarkers related to inflammatory response, and consequently impairs the immune system. Additionally, SDPP supplementation for piglets prevents the reduction on leukocytes levels and the negative effects associated with weight gain, as well as minimizing the inflammatory response, demonstrating that SDPP can modulate the inflammatory processes and consequently may improve the immune system due active proteins presents in SDPP.